1994
DOI: 10.1161/01.cir.90.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Diminished vascular response to inhibition of endothelium-derived nitric oxide and enhanced vasoconstriction to exogenously administered endothelin-1 in clinically healthy smokers.

Abstract: BACKGROUND Smoking is a major risk factor for the development of atherosclerosis. Because endothelial dysfunction may be a marker for future atherosclerosis, we investigated the effects of smoking on endothelium-dependent control of vascular tone. METHODS AND RESULTS The effects of brachial arterial infusions of NG-monomethyl-L-arginine (L-NMMA), a nitric oxide synthesis inhibitor; sodium nitroprusside; endothelin-1; and norepinephrine on forearm blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
113
0
5

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(128 citation statements)
references
References 56 publications
10
113
0
5
Order By: Relevance
“…15,16 However, others have shown that smoking is associated with an acute but transient elevation in ET-1 levels 40 and that only acute, but not chronic, exposure to cigarettes results in an exaggerated vasoconstrictive response to exogenous ET-1 relative to controls. 41 The lack of significant vasodilation with BQ-123 in this study suggests that, compared with hypertension, ET-1 does not contribute substantially to vascular tone in smokers, especially via the ET A receptor. All of the smokers in this study were considered heavy smokers, because they consumed between 10 and 30 cigarettes/d.…”
Section: Et-1 and Vascular Dysfunction In Smokersmentioning
confidence: 56%
“…15,16 However, others have shown that smoking is associated with an acute but transient elevation in ET-1 levels 40 and that only acute, but not chronic, exposure to cigarettes results in an exaggerated vasoconstrictive response to exogenous ET-1 relative to controls. 41 The lack of significant vasodilation with BQ-123 in this study suggests that, compared with hypertension, ET-1 does not contribute substantially to vascular tone in smokers, especially via the ET A receptor. All of the smokers in this study were considered heavy smokers, because they consumed between 10 and 30 cigarettes/d.…”
Section: Et-1 and Vascular Dysfunction In Smokersmentioning
confidence: 56%
“…41 Smoking appears to impair endothelial cell function in many vascular regions, and evidence supports long-term vasoconstriction and altered endothelial response 37,42,43 to various vasoactive mediators in tobacco smoke. 40,44,45 Human studies indicate abnormal choroidal vascular reactivity to carbogen (high oxygen) inhalation in chronic smokers. 30 Substances in cigarette smoke have additionally been demonstrated to induce direct oxidative damage to endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…22 Active tobacco smokers exhibit abnormal vascular reactivity that may contribute to the pathogenesis of smoking-induced cardiovascular disease. Active smoking reduces basal NO release 23 and impairs NO mediated endothelium-dependent relaxation of the forearm 24 and coronary 25 vasculature. Active smoking also causes abnormal constrictor responses in the coronary vasculature.…”
mentioning
confidence: 98%